METHODOLOGICAL FEATURES OF HISTORICAL TYPES OF ECONOMIC THEORY'S SCIENTIFIC RATIONALITY IN TERMS OF MODERN PHILOSOPHY OF SCIENCE - T. Gaidai (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article studies the evolution of basic methodological features of economic theory on its different historical stages.The research highlights the fruitful usage of a new analytical approach on the basis of the achievements of modern philosophy of science. Its presents the research of main types of scientific rationality dominating at certain historical stages of science maturity. Such as historical, classical, nonclassical and postnonclassical types of scientific rationality. Structuring and research of basic methodological features of such historical types of economic theory’s scientific rationality as classical economics (end of ХVII century – 70-th of XIX century), nonclassical economics (70-th of ХІХ century – 70-th of ХХ century), postnonclassical economics (70-th of ХХст. – the beginning of ХХI century) are undertaken. Methodological analysis accentuated ideological, ontological, epistemological dominants and main differences in basic techniques of the main types of economic theory’s scientific rationality. The research argues the illegality of existing in the economics literature attempts to identification or simplified reduction of more mature types of scientific rationality to the less mature. The article shows the contribution made by the leaders of classical, nonclassical and postnonclassical economics in the development of normative and positive economic methodology. It is emphasized a general tendency to methodological pluralism, pluralism of paradigmal structureand interdisciplinary of scientific economic knowledge throughout its historical development.